تكامل عمل الشبكات الكهربائية التقليدية مع مصادر الطاقة المتجددة - شعبان فيصل; خيربك طارق; رزوق سنان (Latakia University Journal -Engineering Sciences Series, 2019)
In most countries, electrical power grids now rely on technologies and systems that have been in existence for more than 50 years, making their old instruction an obstacle to meeting the growing demand for energy and meeting the needs of electricity users. As a result of fast development of electrical power applications, the need to find new ways to produce, store and deliver electricity to the consumer has been directed towards the techniques of generating electricity from renewable energy sources such as solar, wind, biomass and other energy sources, Our traditional power grids today face new challenges, including the involvement of renewable energy resources distributed at different points of the network, or what is known as distributed generation, The disadvantages of this shift from central power generation to decentralized generation are voltage instability and changing power flow within the network. The concept of the smart grid of the energy system has recently been introduced. It is an integrated digital electricity system that effectively controls the production of energy from its various sources. In this paper, we presented a basic understanding of the performance of the traditional electrical grid when integrating with renewable energy resources distributed at different points, and the impact of smart grid technology on resolving the problem of load flow. تعتمد شبكات الطاقة الكهربائية في أغلب البلدان حاليًا على تقنيات وأنظمة مر عليها ما يزيد عن خمسين عامًا، مما يجعل من بنتيها القديمة عائقًا في مواكبة الطلب المتزايد على الطاقة وتلبية احتياجات المستخدمين من الكهرباء. ونتيجة للتطور السريع في تطبيقات الطاقة الكهربائية كانت الحاجة إلى إيجاد سبل جديدة لإنتاج الكهرباء وتخزينها وتوصيلها إلى المستهلك، فكان التوجه نحو تقنيات توليد الطاقة الكهربائية من المصادر المتجددة للطاقة كالطاقة الشمسية وطاقة الرياح والكتلة الحيوية وغيرها من مصادر الطاقة الأخرى، الأمر الذي جعل من شبكات الطاقة الكهربائية التقليدية لدينا اليوم تواجه تحديات جديدة، بما في ذلك إشراك موارد الطاقة المتجددة الموزعة في نقاط مختلفة من الشبكة، أو ما يعرف بالتوليد الموزع (Distributed Generation). مساوئ هذه التحول من التوليد المركزي للطاقة إلى التوليد اللامركزي هي عدم استقرار الجهد وتغير سريان الاستطاعة داخل الشبكة. تم مؤخرا طرح مفهوم الشبكة الذكية لنظام الطاقة، حيث تعد نظامًا كهربائيًا رقميًا متكامل يتم من خلاله التحكم الفعلي في انتاج الطاقة من مصادرها المتنوعة. قدمنا في هذا البحث فهماً أساسياً لأداء الشبكة الكهربائية التقليدية عند التكامل مع موارد الطاقة المتجددة والموزعة في نقاط مختلفة منها، وتأثير تقنية الشبكة الذكية على حل مسألة سريان الحمولة.